The interaction between the major vault protein rs4788186 polymorphism, alcohol dependence, and depression among male Chinese problem drinkers - Wu, Yuyu; Zhao, Ke; Chen, Yingjie; Wu, Liujun; Qiu, Feng; Yuan, Yuying; Shen, Guanghui; Wang, Kexin; Kang, Yimin; Jiang, Yongsheng; Wang, Wei; Chen, Li; et al. (Frontiers in Psychiatry, 2023)
Objective Alcohol use disorder (AUD) is the second most prevalent mental disorder and might be related to depression. Major vault protein (MVP) is a cytoplasmic protein related to vesicle transport. The present study aimed to investigate the interaction between a genetic variant (MVP rs4788186) and depression in adult male Han Chinese with AUD during withdrawal. Methods All participants (N = 435) were diagnosed with AUD. Alcohol dependence level was measured using the Michigan Alcoholism Screening Test, and depression was measured using the self-rating depression scale. Genomic DNA was extracted from peripheral blood and genotyped. Results Hierarchical regression analysis identified an interaction between MVP rs4788186 and alcohol dependence level for depression (β = −0.17, p < 0.05). Then, a region of significance test was performed to interpret the interaction effect. Re-parameterized regression models revealed that the interaction between MVP rs4788186 and alcohol problem severity fit the strong differential susceptibility model (R2 = 0.08, p < 0.001), suggesting that the AA homozygotes would be more likely subjects with the G allele to experience major depression symptoms. Conclusion Carriers of the AA homozygote of MVP rs4788186 may be more susceptible to severe alcohol problems and higher levels of depression during withdrawal.